Improvisation and Radical Objectivization Identities in Angela Carter's The Bloody Chamber: A Lacanian Reading - Thulfiqar Abdulameer Sulaiman Alhmdni (RIRAI Publisher, 2023)
This research applies Lacanian psychoanalysis to scrutinize the use of improvisation and radical objectivization in Angela Carter's The Bloody Chamber. Drawing on Lacan's theory of the